Pengaruh Inklusi Keuangan dan Literasi Keuangan terhadap Kepuasan Pelayanan Keuangan pada Bank Jateng - Nabila Zalfalifia; Tri Nur Wahyudi (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to investigate the effect of financial inclusion and financial literacy on financial service satisfaction at Bank Jateng. The method used in this study is quantitative with associative research design. Data was collected through a questionnaire with a 4-point Likert scale distributed to Bank Jateng customers in several branches in Central Java. The study sample was selected using purposive sampling technique. Data analysis was performed using multiple linear regression with the help of SPSS Version 25 software or software. The results showed that financial inclusion and financial literacy had a significant effect on financial service satisfaction. These findings make an important contribution in improving banking services and supporting more effective policies on financial inclusion and literacy in Indonesia